Maximizing Photosynthesis-Driven Baeyer–Villiger Oxidation Efficiency in Recombinant Synechocystis sp. PCC6803 - Tüllinghoff, Adrian; Uhl, Magdalena B.; Nintzel, Friederike E. H.; Schmid, Andreas; Bühler, Bruno; Toepel, Jörg (Frontiers in Catalysis, 2022)
Photosynthesis-driven whole-cell biocatalysis has great potential to contribute to a sustainable bio-economy since phototrophic cells use light as only energy source. It has yet to be shown that phototrophic microorganisms, such as cyanobacteria, can combine supply of high heterologous enzyme levels with allocation of sufficient reduction equivalents to enable efficient light-driven redox biocatalysis. Here, we demonstrate that the heterologous expression of a NADPH-dependent Baeyer-Villiger monooxygenase (BVMO) gene from Acidovorax sp. CHX100 turns Synechocystis sp. PCC6803 into an efficient oxyfunctionalization biocatalyst, deriving electrons and O2 from photosynthetic water oxidation. Several expression systems were systematically tested and a PnrsB-(Ni2+) controlled expression based on a replicative plasmid yielded the highest intracellular enzyme concentration and activities of up to 60.9 ± 1.0 U gCDW-1. Detailed analysis of reaction parameters, side reactions, and biocatalyst durability revealed – on the one hand – a high in vivo BVMO activity in the range of 6 ± 2 U mgBVMO-1 and – on the other hand – an impairment of biocatalyst performance by product toxicity and by-product inhibition. Scale-up of the reaction to 2-liter fed-batch photo-bioreactors resulted in a stabilization of the bioconversion over several hours with a maximal specific activity of 30.0 ± 0.3 U g CDW-1 and the formation of 2.6 ± 0.1 g of ε-caprolactone. Process simulations based on determined kinetic data revealed that photosynthesis-driven cyclohexanone oxidation on a 2-L-scale under high light conditions was kinetically controlled and not subject to a limitation by photosynthesis.